ROMATOLOJİK HASTALIKLARDA GEN TEDAVİSİNİN YERİ - Feride Göğüş (Archives of Rheumatology, 2000)
The therapeutic use of genes is of quite recent origin. Studies for the treatment of monogenetic and poligenetic diseases are continuing on human and animal models. Genes encoding anti-arthritic products can be transferred to intra or extra-articular sites. Promising data have resulted from the application of these strategies. In this review, principles and application of gene therapy for rheumatic diseases are summarised.